A Hard Look at "Soft" Cost-control Measures in Healthcare Organizations: Evidence from Preferred Drug Policies in Germany - Daniel Avdic; Katharina Blankart (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2021)
Cost-control interventions that target physicians' clinical discretion are common in healthcare, but evidence on their efficacy is scarce; in particular for "soft" policies when liability is unlikely to be enforced by the regulator. We study the effectiveness of preferred drug policies (minimum prescription quotas of specific "preferred" drugs) in altering physicians practice styles within the high volume drug class of HMG-CoA-reductase inhibitors (statins) in the German statutory health insurance system. Using a nationally representative panel of ambulatory care physicians between 2011 and 2014, we exploit the decentralized institutional setting to estimate physician responses to variation in preferred drug policies across regional physician associations over time in a generalized difference-in-differences design. Results show that although the cost-control mechanism increases average policy adherence, this effect is mainly driven by physicians with initially high use rates of preferred drugs. We argue that such misdirection may limit the policy's usefulness in reducing inappropriate practice variation among healthcare providers.
Keywords: I12; I18; O33; H75; 330; Cost-control; Healthcare; Practice Style; Difference-in-differences